Studi Pertumbuhan Sektor Perbankan dari Perspektif Analisis Fundamental Keuangan - Bahri, Nur Alim; Amiruddin, Amiruddin; Rasyid, Syarifuddin; Darmawati , Darmawati; Rahmawati HS (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The aim of this research is to determine the influence of the Current Ratio, Earning Per Share and Debt to Equity Ratio on Stock Prices with the Price Earning Ratio as a Moderating Variable in the Conventional Banking Sector listed on the Indonesia Stock Exchange. This research is a type of quantitative research. The data used in this research is secondary data, with data collection methods using purposive sampling techniques. The population of this research is the conventional banking sector registered on the IDX for the period 2017 to 2021. Then a population of 43 companies was obtained with 25 conventional banking sector companies meeting the criteria. Data analysis techniques use descriptive statistical analysis, classical assumption testing, moderated regression analysis and hypothesis testing. The results of this research found that the Current Ratio and Earning Per Share had a significant effect on share prices, while the Debt to Equity Ratio had the opposite effect. In terms of moderation, the Price Earning Ratio is not able to moderate the Current Ratio and Debt to Equity Ratio on stock prices but cannot moderate the relationship between Debt to Equity Ratio and stock prices.